Explosive invasion of plant mitochondria by a group I intron - Cho, Yangrae (The National Academy of Sciences, 1998)
Group I introns are mobile, self-splicing genetic elements found principally in organellar genomes and nuclear rRNA genes. The only group I intron known from mitochondrial genomes of vascular plants is located in the cox1 gene of Peperomia, where it is thought to have been recently acquired by lateral transfer from a fungal donor. Southern-blot surveys of 335 diverse genera of land plants now show that this intron is in fact widespread among angiosperm cox1 genes, but with an exceptionally patchy phylogenetic distribution. Four lines of evidence—the intron’s highly disjunct distribution, many incongruencies between intron and organismal phylogenies, and two sources of evidence from exonic coconversion tracts—lead us to conclude that the 48 angiosperm genera found to contain this cox1 intron acquired it by 32 separate horizontal transfer events. Extrapolating to the over 13,500 genera of angiosperms, we estimate that this intron has invaded cox1 genes by cross-species horizontal transfer over 1,000 times during angiosperm evolution. This massive wave of lateral transfers is of entirely recent occurrence, perhaps triggered by some key shift in the intron’s invasiveness within angiosperms.